2020
DOI: 10.1186/s13098-020-00538-y
|View full text |Cite
|
Sign up to set email alerts
|

Leu124Serfs*26, a novel AGPAT2 mutation in congenital generalized lipodystrophy with early cardiovascular complications

Abstract: Background: Congenital generalized lipodystrophy (CGL) is a rare autosomal recessive disorder characterized by the near-total loss of subcutaneous adipose tissue soon after birth, resulting in ectopic fat deposition and severe metabolic disturbances. Most cases are caused by AGPAT2 or BSCL2 gene mutations. We aimed to report two unrelated CGL patients with a novel frameshift mutation in AGPAT2 (p.Leu124Serfs*26). Methods: Clinical features and laboratory were obtained by medical interview and medical records r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Akinci et al. ( 11 ) reported the median onset of hypertriglyceridemia and hepatic steatosis at 14 years and 16 years of age respectively, however cases of earlier development are fairly common ( 10 , 23 28 ). Genotype – phenotype correlations have also been described: in BSCL type 1, females tend to develop diabetes and acanthosis nigricans more than males ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akinci et al. ( 11 ) reported the median onset of hypertriglyceridemia and hepatic steatosis at 14 years and 16 years of age respectively, however cases of earlier development are fairly common ( 10 , 23 28 ). Genotype – phenotype correlations have also been described: in BSCL type 1, females tend to develop diabetes and acanthosis nigricans more than males ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pathways include metabolism [ [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [134], ASB1 [135], OSM (oncostatin M)…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by a loss of subcutaneous adipose tissue and marked insulin resistance, with consequences including diabetes, hypertriglyceridemia, hepatic steatosis, polycystic ovary syndrome, acanthosis nigricans , and arterial hypertension 2 . Early myocardial revascularization and cases of multivessel coronary disease leading to acute myocardial infarction in a young patient (29 years) have been described 3 . We have previously described infections, liver complications, and cardiovascular disease (CVD) as causes of death in CGL patients 4 .…”
Section: All Ccs+ Ccs− P Valueamentioning
confidence: 99%
“…2 Early myocardial revascularization and cases of multivessel coronary disease leading to acute myocardial infarction in a young patient (29 years) have been described. 3 We have previously described infections, liver complications, and cardiovascular disease (CVD) as causes of death in CGL patients. 4 Deaths from CVD have been reported in patients between 20 and 62 years of age, and necropsy studies have reported stiffness of intramural coronary arteries with intimal fibrosis and subendocardial collagen deposition.…”
mentioning
confidence: 99%